2006
DOI: 10.1182/blood-2005-08-3121
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DPB1 matching status has significant implications for recipients of unrelated donor stem cell transplants

Abstract: Studies in unrelated donor (UD) hematopoietic stem cell transplantations (HSCT)show an effect of the matching status of HLA-DPB1 on complications. We analyzed 423 UD-HSCT pairs. Most protocols included T-cell depletion (TCD). All pairs had high-resolution tissue typing performed for 6 HLA loci. Two hundred eightytwo pairs were matched at 10 of 10 alleles (29% were DPB1 matched). In 141 HLAmismatched pairs, 28% were matched for DPB1. In the 10 of 10 matched pairs (n ‫؍‬ 282), the 3-year probability of relapse w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 37 publications
9
73
2
3
Order By: Relevance
“…Another article, that is published by Shaw et al, reported a higher relapse rate in HLA-DPB1-matched pairs as compared with HLA-DPB1-mismatched pairs in a group of 10/10 matched T-cell depleted unrelated ASCTs. 14 In this study, researchers observed a higher rate of aG-VHD, without a difference in TRM or OS in HLA-DPB1 mismatched transplantations. Fleischhauer et al reported an increased risk of graft failure with the presence of nonpermissive HLA-DPB1 mismatches, in a group of unrelated ASCT for betathalassemia patients.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Another article, that is published by Shaw et al, reported a higher relapse rate in HLA-DPB1-matched pairs as compared with HLA-DPB1-mismatched pairs in a group of 10/10 matched T-cell depleted unrelated ASCTs. 14 In this study, researchers observed a higher rate of aG-VHD, without a difference in TRM or OS in HLA-DPB1 mismatched transplantations. Fleischhauer et al reported an increased risk of graft failure with the presence of nonpermissive HLA-DPB1 mismatches, in a group of unrelated ASCT for betathalassemia patients.…”
Section: Discussionmentioning
confidence: 55%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] For instance, in the study by Loiseau et al reported increased frequency of severe aGVHD and poorer survival in two HLA-DP incompatibilities in a group of unrelated ASCT patients. 10 In this study they were not able show a significant relationship between HLA-DP mismatches and disease relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting results have been reported on the relative importance of various class I and II loci mismatches on outcome. [21][22][23][24][25][26][27][28] Early studies reported that low-resolution mismatches at HLA-A and -B Ags, and high-resolution mismatches at HLA-DRB1 allele are associated with worse GvHD and survival. [21][22] Matching algorithms favoured class II matching over class I matching when a complete match could not be found.…”
Section: Matching Criteriamentioning
confidence: 99%
“…Statistically, relapse was significantly higher among HLA-DPB1-matched patients (74%) as compared with HLA-DPB1-mismatched patients (56%, P ¼ 0.001). 28 A large National Marrow Donor Program (NMDP) study reported that single low-resolution mismatches for both class I (including HLA-C) and for DRB1 loci are independently associated with a significantly higher risk of graft rejection, GvHD and mortality, as compared with full matching. This observation suggests that HLA-C typing should be included in search algorithms.…”
Section: Matching Criteriamentioning
confidence: 99%
“…Bronwen Shaw began by providing a summary of her work at the ANRI and the ANT experience in this area. [2][3][4] She presented data on 423 UD-HSCT performed between 1996 and 2003 for whom four digit molecular tissue typing for 12 alleles and clinical follow-up data were available. The percentage of wellmatched (10/10) donor-recipient pairs (67%) in the ANT study was greater than that in any other study (44% in the Japanese Marrow Donor Programme study 5 and 47% in the Fred Hutchinson Cancer Research Center study 6 ), in part due to the time period over which the study was performed.…”
Section: Donor Selection and Transplant Outcomementioning
confidence: 99%